(untitled) (International Journal of Studies in Nursing, 2022)
Self-care is often lacking in nursing students worldwide. The objectives for this study were to discover the current self-care practices of one group of entry level undergraduate nursing students, the students’ understanding of self-care, and the students’ preferences for self-care interventions aimed at improving self-care. Quantitative and quantitative measures were used to measure the students’ current self-care practices, needs, and recommendations for interventions to be used in future semesters to improve nursing student self-care. The students were found to generally be deficient in areas related to nutrition, obtaining healthcare information or guidance, pacing themselves to avoid exhaustion, and performing relaxation exercises. They scored well on areas related to psychosocial self-care, such as believing their life has meaning or having meaningful relationships. Several suggestions were made by the students for encouraging nursing student self-care. Nursing students are often lacking in self-care. It is important for nursing programs worldwide to develop and encourage student self-care.